Publisher, Publication and Price: Impact on Library Acquisition - A Case Study - Meera, B. M. (Journal of Information and Knowledge, 2014)
This article presents a case study of the correlation between the number of books brought out by different publishers in a particular subject, with the price escalation and sinking budget. Acqisition of book in Statistics in the Indian Statistical Institute (Bangalore Centre) Library over Three years is taken for the sample study.